2011
DOI: 10.1007/s12028-011-9509-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcome of Seizures After Chronic Subdural Hematoma

Abstract: Lower mean GCS on admission is independently predictive of seizures, most of which occur within the first three months after CSDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…In the literature, the proportion of patients with bilateral hematomas ranges between 10 to 30% [12,13,15,28]. In our cohort, 28% of patients had bilateral hematomas and these patients had an approximately 4-fold greater risk of surgical complications than patients with a single hematoma.…”
Section: Reoperation As a Results Of Surgical Complicationsmentioning
confidence: 70%
See 1 more Smart Citation
“…In the literature, the proportion of patients with bilateral hematomas ranges between 10 to 30% [12,13,15,28]. In our cohort, 28% of patients had bilateral hematomas and these patients had an approximately 4-fold greater risk of surgical complications than patients with a single hematoma.…”
Section: Reoperation As a Results Of Surgical Complicationsmentioning
confidence: 70%
“…Numerous studies have assessed the risk factors for recurrence, with over 20 different factors identified, highlighting the complexity and heterogeneity of this condition [6,7,[12][13][14]20,22].…”
Section: Reoperation Caused By Recurrent Hematomasmentioning
confidence: 99%
“…The latter rate is similar to the one experienced by TBI without SDH. The risk of developing seizures in patients with chronic SDH ranges between 2.3 and 17 % depending on the type and severity of the head injury [12][13][14][15][16]. Clinical and radiological risk factors for developing seizures associated with chronic SDH include brain atrophy, mixed-density SDH, prior stroke, and low Glasgow Coma Scale (GCS) at presentation [16][17][18].…”
Section: Epidemiology Of Seizures In Subdural Hematomamentioning
confidence: 99%
“…The risk of developing seizures in patients with chronic SDH ranges between 2.3 and 17 % depending on the type and severity of the head injury [12][13][14][15][16]. Clinical and radiological risk factors for developing seizures associated with chronic SDH include brain atrophy, mixed-density SDH, prior stroke, and low Glasgow Coma Scale (GCS) at presentation [16][17][18]. In patients with chronic SDH who underwent surgical intervention, the incidence of seizures is between 5 and 22 % in the acute postoperative period [17][18][19][20][21].…”
Section: Epidemiology Of Seizures In Subdural Hematomamentioning
confidence: 99%
See 1 more Smart Citation